Sosialisasi Perlindungan Konsumen dalam Islam di Desa Nusa Makmur Kecamatan Air Kumbang - Choirunnisak Choirunnisak (AKM, 2021)
This community service activity discusses the introduction of the history of consumer protection in Islam, the argument for consumer protection, consumer rights, and consumer obligations. The purpose of this community service activity is to provide an introduction to consumer protection for recitation scholars in the village of Nusa Makmur. With the hope that participants can understand the rights and obligations of consumers and consumer protection.